Seasonality affects the below-ground bud bank dynamics of the Cerrado - Ferraro, Alexandre; Silva, Gabriela S.; Martins, Aline R. [UNESP]; Piedade, Sônia Maria De S.; Fidelis, Alessandra [UNESP]; Appezzato-da-Glória, Beatriz (Wiley, 2022)
Question: How does seasonality affect the below-ground bud bank dynamics in open savannas from the Cerrado and the density of below-ground bud-bearing organs? As the Cerrado is subject to marked seasonality, many herbaceous plants may lose their above-ground biomass during the dry season, and regenerate it later in the rainy period through resprouting from below-ground buds. Herein, we tested the hypothesis that seasonality may directly affect bud bank dynamics and below-ground bud-bearing organs, with a larger bud bank size and higher densities of below-ground organs in the rainy season. Location: Open savannas of the Cerrado, southeastern Brazil. Methods: The bud bank was sampled in three open areas of the Cerrado. In each area, 10 plots were established, and, within each plot, the biomass was sampled to 10 cm below-ground level. In the lab, buds and below-ground organs were counted. We fitted generalized linear mixed models (GLMM) to test the differences in the bud bank and the below-ground organ densities between the dry and rainy seasons. Results: The bud bank size was smaller in the dry season. Buds found in the dry season suggest they were developed in the rainy season and remained dormant, not forming new shoots. Non-woody rhizomes of caespitose grasses were more abundant during the rainy season. Xylopodia and woody rhizome densities were not significantly affected by seasonality. Conclusions: Bud bank dynamics in the Cerrado is affected by seasonality. There is a decrease in bud bank density in the dry season, suggesting that buds were developed into new branches in the rainy season, but not all of them develop into new shoots in the same season. Thus, the bud bank evaluated in the dry season probably is formed by an accumulation of dormant preformed buds, highlighting the occurrence of a resprouting dynamic of native species of the Cerrado in the rainy season.
Keywords: buds; Cerrado; dormancy; phenology; resprouting; rhizomes; savanna; seasonality; xylopodia